STRUCTURAL AND MORPHOLOGICAL CHARACTERISTICS OF PLASMA SPRAYED TiO2-COATINGS - Dwi Bayuwati (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2012)
STRUCTURAL AND MORPHOLOGICAL CHARACTERISTICS OF PLASMA SPRAYED TiO2-COATINGS. TiO2 thin layers have been deposited on glass substrates using Plasma Spray technique. The TiO2 starting powders are a laboratory grade commercial powders. Before spraying, to check the availability of the basic material for Plasma Spray technique, a series of characterization was conducted. The TiO2 starting powders were identified its particle size using Particle Size Analyzer (PSA) resulting diameter at 90% was 42.72 µm. X-Ray Diffractometer (XRD) measurement was done to identify the peaks of the basic material elements using Kα radiation at wavelength 1.5406 Å resulted TiO2 of Anatase structure. Spray dry process was then conducted in order to get circular and free flowing particles for feedstock of plasma spray system. Distribution of particles showed a dominat of 20 µm diameter-free flowing particle. Plasma Spray process of TiO2 powder furthermore was conducted on slide glass microscope under several parameter conditions such as power, flame-substrate distance and preheating treatment variation. The TiO2/glass coatings with variation of flame-substrate distance (10 and 12 cm) resulted in 5.806 µm and 4.913 µm layer thickness with grain size in the range of 0.8-2 mand 1-2.8 µm, respectively. XRD diffractogram results revealed that the TiO2 layer are dominat in rutile phase but at a little higher of plasma power, low anatase phase existed. The preheated-plasma sprayed TiO2 coatings were visibly difussed into the glass substrate and resulted in dominat rutile phase (at 2 cycles preheating) but not existed in a longer preheating time (4 cycles preheating treatment).